1989
DOI: 10.1002/bin.2360040105
|View full text |Cite
|
Sign up to set email alerts
|

The use of brief restraint plus reinforcement to treat self‐injurious behavior

Abstract: This study evaluated the use of brief arm restraint plus differential reinforcement of alternative behavior to treat the self-injurious behavior of two residents with multiple handicaps and profound mental retardation. The study took place in a nursing home and sessions were conducted for 15 minutes, Monday through Friday. The design contained both multiple baseline and reversal components. Mean levels of self-injurious behavior and stripping for one client were reduced from 92 to 16% and 81 to 2%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…use of verbal instruction to interrupt a behaviour) restraint. Konarski & Johnson (1989) found that use of DRA alongside restraint was successful in reducing both SIB and inappropriate behaviours. A recent study by Johnson et al (1994) also gives strong support to the concept of multi-modal interventions.…”
Section: Introductionmentioning
confidence: 98%
“…use of verbal instruction to interrupt a behaviour) restraint. Konarski & Johnson (1989) found that use of DRA alongside restraint was successful in reducing both SIB and inappropriate behaviours. A recent study by Johnson et al (1994) also gives strong support to the concept of multi-modal interventions.…”
Section: Introductionmentioning
confidence: 98%
“…The importance of this study is underlined by the sample size, the severity of the self-injurious behaviours treated, the variety of hypothesised functions served by the individual's self-injury, the practicality of the intervention procedure and the maintenance of treatment gains for up to four years. The effectiveness of this treatment package has also been demonstrated for selfinjury apparently maintained by sensory reinforcement (Day et al, 1988;Saloviita, 1988) or of unknown motivation (Konarski & Johnson, 1989).…”
Section: Basing Intervention On Analysismentioning
confidence: 89%
“…Azrin et al (1988), for example, report that a DRI plus response interruption and brief restraint procedure was, in general, considerably more effective in reducing the severe selfinjury shown by eight severely or profoundly handicapped adults and one autistic girl than DRO, DRI or response interruption procedures alone. The effectiveness of this treatment package has also been demonstrated for selfinjury apparently maintained by sensory reinforcement (Day et al, 1988;Saloviita, 1988) or of unknown motivation (Konarski & Johnson, 1989). The effectiveness of this treatment package has also been demonstrated for selfinjury apparently maintained by sensory reinforcement (Day et al, 1988;Saloviita, 1988) or of unknown motivation (Konarski & Johnson, 1989).…”
Section: Basing Intervention On Analysismentioning
confidence: 95%